Irony as a Way of Life? Truth and Irony: Philosophical Meditations on Erasmus, Terence J.Martin, Catholic University of America Press, 2015 (ISBN 978‐0‐8132‐2809‐9), xii + 259 pp., hb 65A Case for Irony, JonathanLear, Harvard University Press, 2011 (ISBN 978‐0‐6744‐1688‐8), xiv + 210 pp., pb £15.95. Issue 2 (April 2017) - Ravenscroft, Simon
Abstract: As a figure of speech for which a speaker's meaning is taken to be the opposite of what she says, irony may not ordinarily be linked to truthfulness. Two recent books by Terence J. Martin and Jonathan Lear nonetheless mount convincing cases for a more complex, philosophical understanding of irony as non‐cynical, and as having a constructive role to play in the truthful and well‐lived life. Taking Erasmus, and Socrates and Kierkegaard as their main sources respectively, both authors argue that the experience of irony allows for a specific form of truthfulness to emerge about who we are as finite beings. This review essay leads with an analysis of the argument developed in defence of this point in Martin's book on Erasmus, before bringing Lear into the conversation in order to reveal shortcomings in Martin's theorisation of irony. This is followed by a critical response to Lear's own account, which allows for further reflection on the relation between irony, religion, and theology in his and Martin's main sources.